Neuroprotective Effects of Antioxidants in Alzheimer's Dementia: A Literature Review - Komang Trisna Sumadewi; Saktivi Harkitasari; Ni Putu Diah Witari; Fransiscus Fiano Anthony (Jurnal Sehat Indonesia (JUSINDO), 2026)
This research aims to analyze the neuroprotective effects of antioxidants in Alzheimer’s disease (AD) by examining their roles in mitigating oxidative stress and related pathological mechanisms. The research employs a qualitative design with a descriptive approach through a literature review, utilizing secondary data from peer-reviewed scientific articles and relevant academic sources. Data were collected through systematic literature searching and analyzed using thematic qualitative methods, including data reduction, categorization, and inductive interpretation. The findings indicate that oxidative stress plays a central role in AD pathogenesis by interacting with amyloid-beta accumulation, tau hyperphosphorylation, mitochondrial dysfunction, neuroinflammation, and metabolic dysregulation. Antioxidants, particularly mitochondria-targeted compounds and natural bioactive substances such as polyphenols and flavonoids, demonstrate significant neuroprotective potential through multi-target mechanisms. However, their clinical effectiveness is limited by factors such as low bioavailability and restricted blood–brain barrier penetration. These findings highlight the importance of developing multi-target therapeutic strategies and advanced drug delivery systems to enhance treatment efficacy. In conclusion, this study contributes to a deeper understanding of the role of antioxidants in AD and supports the shift toward integrative and system-based approaches in neurodegenerative disease management.